2019
DOI: 10.1103/physrevb.99.104303
|View full text |Cite
|
Sign up to set email alerts
|

Floquet time crystals in clock models

Abstract: We construct a class of period-n-tupling discrete time crystals based on Zn clock variables, for all the integers n. We consider two classes of systems where this phenomenology occurs, disordered models with short-range interactions and fully connected models. In the case of short-range models we provide a complete classification of time-crystal phases for generic n. For the specific cases of n = 3 and n = 4 we study in details the dynamics by means of exact diagonalisation. In both cases, through an extensive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 64 publications
1
68
0
Order By: Relevance
“…Our quantum simulator is therefore a versatile and reliable experimental setup useful for investigating exotic properties of discrete and continuous Abelian lattice gauge theories [40,41]. Possible outlook for this work is the extension to two-dimensional theories, in continuity with a recent proposal about the study of 2D pure gauge systems [42], as well as the application of this protocol for simulating clock variables to different models such as time crystals [43,44].…”
mentioning
confidence: 99%
“…Our quantum simulator is therefore a versatile and reliable experimental setup useful for investigating exotic properties of discrete and continuous Abelian lattice gauge theories [40,41]. Possible outlook for this work is the extension to two-dimensional theories, in continuity with a recent proposal about the study of 2D pure gauge systems [42], as well as the application of this protocol for simulating clock variables to different models such as time crystals [43,44].…”
mentioning
confidence: 99%
“…Intriguingly, recent research efforts have shown that it is possible to realize a robust DTC in the absence of disorder [40,41,[52][53][54][55][56]. This surprising observation implies the presence of mechanisms other than MBL that can prevent Floquet systems from heating up.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to qualify as a genuine non-equilibrium phase of matter, these sub-harmonic oscillations must persist at long times (t/T 1), without fine tuning the Hamiltonian parameters [40,41]. Through several theoretical and experimental studies, the existence of the DTC phase has now been firmly established [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…Let us stress once more that, although most recent developments concerning the realization of quantum time crystals have mainly resorted to the introduction of a fine-tuned external periodic drive in the spirit of Floquet time crystals [9,4,15,12,16,17,18], we only consider models with timeindependent Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%